Case report: Case report and literature review: Treatment of sweat gland carcinoma - Dai, Yuhong; Feng, Jin; Zhou, Xiao (Frontiers in Oncology, 2023)
Background: Sweat gland carcinoma (SGC) is a rare neoplasm originating from sweat glands. Surgical resection is the first choice for SGC treatment and there is no consensus on other treatments for advanced SGC. Methods and results: In this case report, we represent a case of a female patient with advanced SGC who received surgery, radiotherapy, multiple lines chemotherapy which include Docetaxel, nedaplatin, Albumin-bound paclitaxel, pemetrexed and immunotherapy which is Camrelizumab. The survival time of this patient is 35 months. The MRI tumor monitoring indicated that these treatments slowed the progression of the disease. The effectiveness of chemotherapy, radiotherapy and immunotherapy should be tested for more patients with SGC in the future. Conclusion: Although the patient’s tumor was uncontrolled eventually, multiple treatments delayed tumor growth over a period of time, providing ideas for others when choosing regimens.